Global Research on Palm Oil Diseases and Infections: A Bibliometric Analysis - Saputra, Fahmi Achmad; Mustika, Indria Puti; Safarida, Anna; Sriherwanto, Catur; Putra, Nicky Rahmana (Makara Journal of Technology, 2026)
The sustainability of global palm oil production faces significant threats from a range of diseases and infections affecting palm oil crops. This study presents a comprehensive bibliometric analysis to map the scientific landscape and evolution of research related to palm oil diseases over the past decade. Using data from the Scopus database, 366 relevant documents were analyzed using R and VOSviewer to uncover trends in publication volume, citation impact, prolific authors, country contributions, and keyword co-occurrence networks. The findings reveal a strong research concentration on G. boninense, highlighting its critical role as a persistent pathogen in oil palm plantations. Emerging themes, such as bioactive compound research, comparative biology, and plant–microbiome interactions, reflect the growing interdisciplinary interest in sustainable disease management. This study identified key research gaps and proposed future directions, including molecular breeding, biocontrol strategies, and valorization of bioactive compounds from oil palm by-products. The results offer strategic insights to guide future scientific inquiry and inform sustainable solutions for global palm oil production.